Job design in the function of improving the job performance of the employees in Bosnia and Herzegovinian companies - Alma Kovačević; Adisa Delić (Economic Review: Journal of Economics and Business, 2019)
Due to continuous and radical changes in the contemporary business environment, compa-nies now need to search for new modalities for a strategic positioning in the global market. New ways are sought to build and preserve competitive advantages, thus recognising that knowledge and learning are the key factors of success in the new economy. As a consequence, there is a need to give an ever-growing importance to human resource management in modern companies. Employees and their knowledge are the cornerstone of building competitive advantages only if their perfor-mance is at a desired level, which indicates that job performance management is one of the important managerial tasks. Employee performance is influenced by a multitude of factors, most of which are related to job design. Therefore, this paper aims to analyse the dimensions of organisational structure as an important determinant of job design in the companies in Bosnia and Herzegovina (BiH). The research covered 120 BiH companies, taking into account territorial and business dispersion. The main results of the research are reflected in the understanding of the relationship between the number of employees and the size of company, as well as in the fact that the increase in the number of employees in the company results in the decrease of the number of employees with a university degree compared to employees with high school degree. It should be emphasised in particular that the results of this paper show that within the analysed companies in BiH, the most frequent is the functional organisational structure and that BiH companies are domi-nated by a bureaucratic/mechanical job desi-gn approach that has a negative effect on the achievement of employees' work performance.
Keywords: M10; L20; G22; 330; human resources; job design; job performance; dimension of organisational structure